Closing Wells; Fossil Exploration and Abandonment in the Energy Transition - Inge van den Bijgaart; Mauricio Rodriguez (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Despite ambitious climate goals and already substantial stocks of developed fossil energy reserves, development of new fossil energy reserves continues to be high. This raises concerns, as it reinforces the fossil industry's opportunities and incentives to continue extraction, and may necessitate abandonment of developed fossil reserves to meet climate targets. In this paper, we analyze the energy transition, considering fossil exploration and development activities. We provide conditions for when the fossil industry will abandon reserves, and establish that continued exploration of fossil resources is not incompatible with abandoning developed reserves. The first-best implementation of a carbon budget always involves reserve abandonment, and thus exploration that pushes developed reserves in excess of the remaining budget. A quantitative assessment reveals that a volume equal to 9-19% of current oil and gas reserves are optimally abandoned, and that, even under a 1.5oC warming target, positive exploration of new reserves is justified for another decade.
Keywords: Q21; Q31; Q35; Q54; Q58; 330; carbon budget; energy transition; fossil exploration; non-renewable resources; renewable energy; stranded assets